Evolutionary Relationship between Two Firefly Species, Curtos costipennis and C. okinawanus (Coleoptera, Lampyridae), in the Ryukyu Islands of Japan Revealed by the Mitochondrial and Nuclear DNA Sequences - Masahiko Muraji; Norio Arakaki; Shigeo Tanizaki (The Scientific World Journal)
The phylogenetic relationship, biogeography, and evolutionary history of closely related two firefly species, Curtos costipennis and C. okinawanus, distributed in the Ryukyu Islands of Japan were examined based on nucleotide sequences of mitochondrial (2.2 kb long) and nuclear (1.1-1.2 kb long) DNAs. In these analyses, individuals were divided among three genetically distinct local groups, C. costipennis in the Amami region, C. okinawanus in the Okinawa region, and C. costipennis in the Sakishima region. Their mtDNA sequences suggested that ancestral C. costipennis population was first separated between the Central and Southern Ryukyu areas, and the northern half was then subdivided between C. costipennis in the Amami and C. okinawanus in the Okinawa. The application of the molecular evolutionary clocks of coleopteran insects indicated that their vicariance occurred 1.0–1.4 million years ago, suggesting the influence of submergence and subdivision of a paleopeninsula extending between the Ryukyu Islands and continental China through Taiwan in the early Pleistocene.